A call for a research agenda on fair NLP for Portuguese - de Lima, Luiz Fernando F. P.; de Araujo, Renata Mendes (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2023.233763, 2023)
Diverse areas widely apply artificial intelligence and natural language processing (NLP) tools to their contexts. However, these algorithms present ethical issues, such as biased and discriminatory decisions. For example, representation biases in NLP can result in discriminatory behavior towards race and gender. Works have been addressing this issue and seeking to build fair NLP solutions, however they mainly focus on Anglo-Saxon languages. This work aims to challenge the scientific community in order to stimulate and motivate further research in the fair NLP specifically for the Portuguese language. To achieve this, a literature review was conducted to identify existing research efforts and indicate future directions.